Laparoscopic excision of pancreatic duplication cysts in an asymptomatic infant - Christine G. DeFilippo; Nikhil R. Shah; Rui-Min D. Mao; Taylor P. Williams; Harshwardhan Thaker; Ravi S. Radhakrishnan (Elsevier, 2022)
Pancreatic cysts are a rare subgroup of enteric duplication cysts with approximately 25 published cases in the literature. Awareness of this congenital abnormality and options for treatment are important given the often symptomatic nature and risk of malignant transformation. We present a case of prenatally diagnosed pancreatic duplication cysts successfully managed with laparoscopic surgical excision in a three-month-old male.